Integrated biostratigraphy of the middle to upper Eocene Kırkgeçit Formation (Baskil section, Elazığ, eastern Turkey): larger benthic foraminiferal perspective - Özcan, Ercan; Less, Gy.; Jovane, L.; Catanzariti, R.; Frontalini, F.; Coccioni, R.; Asgharian Rostami, M. (Springer Science and Business Media B.V., 2019)
The Baskil section, located to the west of Elazığ in eastern Turkey, represents deep-marine facies of the Eocene Kırkgeçit Formation, deposited in a wide spectrum of environmental conditions ranging from shelf to basin. The 390-m-thick sequence was deposited at bathyal depths in the Tethys, at the edge of the subsiding Anatolide–Tauride plate and is highly promising for an integrated study of Bartonian to earliest Priabonian mid-latitude neritic and deep-marine biota. The section contains numerous allochthonous limestone beds, characterized either by turbidites or debris flows with resedimented larger benthic foraminifera (LBF). The section spans the planktonic foraminiferal Zones E10/11 to E14, the calcareous nannofossil zones NP15–NP18, shallow benthic zones (SBZ) SBZ16/17 to SBZ18A, including orthophragminid (OZ) zones OZ12–OZ14. The Bartonian–Priabonian boundary is placed at NP17/18 boundary by the lowest occurrence of Chiasmolithus oamaruensis, which lies within Subchron C17n.1n and Zone SBZ18A. The LBF, obtained as loose specimens from 17 turbiditic and debris flow beds, are characterized predominantly by 21 orthophragminid lineages and 13 nummulitid species as well as some other stratigraphically diagnostic genera. Most of the orthophragminid lineages straddle the Bartonian–Priabonian boundary, whereas Orbitoclypeus douvillei and Discocyclina pulcra appear to be the only orthophragminids confined to SBZ17 at its upper range. The Nummulites fabianii-lineage first appearing in zones E12 and NP16 in the Bartonian shows a well-documented evolution of the embryon, and is referred to Nummulites garganicus in the Bartonian, whereas its successor Nummulites hormoensis straddles the Bartonian/Priabonian boundary. The first appearances of N. hormoensis and Heterostegina armenica as well as the last occurrences of Nummulites ptukhiani and Assilina exponens in the section are almost coeval and are utilized to mark SBZ17–18 boundary. The first appearance of the H. armenica-lineage is recorded in zones E14 and upper part of NP17. Two important species, Chapmanina gassinensis and Silvestriella tetraedra, have been first recorded in SBZ18A just above the Bartonian–Priabonian boundary. Thus, the transition of N. garganicus to N. hormoensis, the first appearances of H. armenica, C. gassinensis and S. tetraedra as well as the last occurrences of N. ptukhiani, Assilina exponens, Discocyclina pulcra and Orbitoclypeus douvillei, all across the SBZ17–18 boundary or within the SBZ18A, appear to be the most useful bioevents in the transition from the Bartonian to the Priabonian in shallow-marine realms. © 2019, Springer Nature Switzerland AG.
Keywords: Bartonian–Priabonian; Calcareous nannoplankton; E Turkey; Larger benthic foraminifera; Magnetostratigraphy; Planktic foraminifera